If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + a = b + -1 Reorder the terms: 1 + a = -1 + b Solving 1 + a = -1 + b Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + a = -1 + -1 + b Combine like terms: 1 + -1 = 0 0 + a = -1 + -1 + b a = -1 + -1 + b Combine like terms: -1 + -1 = -2 a = -2 + b Simplifying a = -2 + b
| 8n-30=42 | | 4p+3q=26 | | (x+-2)(x+-2)=-25 | | 400=16t | | 12x^2+25x-7=0 | | 7m+7n= | | 2x+4x+3y= | | 79-4x=23x+19 | | (n-5)*7=35 | | (n-6)*4=40 | | -171x-9x=10x+19 | | 3x+x/2=15 | | 3a-4=0 | | 8x+3=x+38 | | x*2=8 | | 4x*5x=20 | | 4x+3x=12 | | 4x+5x=200 | | 4x+5x=10 | | 4x+5x=100 | | 4yx+5x=20 | | 4x+5y=5y | | b-8=10 | | 5x+4y=31 | | a-8=4 | | 2y-15+3y+3=24 | | z-5=r | | a+9=16 | | 2s+4t-2s-3t= | | 8z=-104 | | 5x=-65 | | 74-6x=12x+18 |